Internalization of Spiritual Values in a Multicultural Society: A Case Study at Tokyo Indonesian School - Akmal, Miftahul Jannah; Syahidin, Syahidin; Fakhruddin, Agus (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
This study aims to analyze the internalization of spiritual values in the Tokyo Indonesian School in the context of the multicultural environment of Japan. This study uses a qualitative approach with a case study method to explore how spiritual values, especially Islamic teachings, are integrated into education at the Tokyo Indonesian School, which has students from diverse cultural and religious backgrounds. Data were collected through in-depth interviews, participant observation, and documentation studies, which were analyzed using the Miles and Huberman model. The results of the study indicate that the Tokyo Indonesian School implements a holistic approach to the internalization of spiritual values with five main steps: i) religious education that focuses on understanding monotheism as the core of faith, ii) the habit of daily worship such as congregational prayer that strengthens discipline and spiritual awareness, iii) the implementation of the Madrasah Diniyah (Madin) program to deepen worship and religious knowledge, iv) the integration of universal values such as discipline, order, and hard work that are relevant to Japanese culture, and v) strengthening student character through teacher role models and harmonious social interactions. Moreover, Sekolah Indonesia Tokyo also strengthens students' spiritual relationship with Allah through religious activities at the mosque facilities near the school. It teaches Japanese cultural values that are in line with Islamic teachings. The implications of this study indicate that inclusive spiritual value-based education can shape students' character, enrich multicultural interactions, and maintain students' cultural and religious identities abroad.